Inquiring into the Railroad Workers' Disease: A Journey through a Triple Discovery and the Nature of Science - Azevedo, Nathalia Helena; Del-Corso, Thiago Marinho [UNESP] (University of California Press, 2024)
This article presents a historical and investigative narrative, The Railway Workers' Disease,to actively engage students in science. The case focuses on the research challenges encountered by Carlos Chagas in Brazil in the early twentieth century. Chagas eventually identified a new disease, the previously unknown protozoan that caused it, and the insect vector that transmitted it: a remarkable triple discovery. By situating inquiry in a historical scenario, teachers can place students in the shoes of actual historical scientists and pose inquiry questions in an authentic context. Our students expressed a sense of being active participants alongside Carlos in conducting a scientific investigation and reported a deeper understanding of scientific practices than in their regular classes. The interactive storytelling and discussion method also enables inquiry learning about the nature of science, in addition to the standard textbook concepts of infectious diseases, protozoa, and the ecology of parasitic insects.
Keywords: Chagas disease; historical narrative; history of science; inquiry-based learning; nature of science; protozoan; scientific literacy